An α‐Helix‐Mimicking 12, 13‐Helix: Designed α/β/γ‐Foldamers as Selective Inhibitors of Protein–Protein Interactions. Issue 37 (28th July 2016) - Grison, Claire M.; Miles, Jennifer A.; Robin, Sylvie; Wilson, Andrew J.; Aitken, David J.
Abstract: A major current challenge in bioorganic chemistry is the identification of effective mimics of protein secondary structures that act as inhibitors of protein–protein interactions (PPIs). In this work, trans ‐2‐aminocyclobutanecarboxylic acid ( t ACBC) was used as the key β‐amino acid component in the design of α/β/γ‐ peptides to structurally mimic a native α‐helix. Suitably functionalized α/β/γ‐peptides assume an α‐helix‐mimicking 12, 13‐helix conformation in solution, exhibit enhanced proteolytic stability in comparison to the wild‐type α‐peptide parent sequence from which they are derived, and act as selective inhibitors of the p53/ h DM2 interaction. Abstract : Match and mimic : α/β/γ‐ Peptides featuring trans ‐2‐aminocyclobutanecarboxylic acid ( t ACBC) as the "structuring" β‐amino acid component adopt a 12, 13‐helical conformation and can behave as selective inhibitors of the p53/ h DM2 interaction.